The Semantic Effect of Repetition of Ibn Kamal Pasha (940H) in his Interpretation - DR. Jumana Abdul Mahdi jasim (Journal of College of Education, 2024)
Repetition is considered one of the features of the Arabic language, which discriminates it from other existing languages. So, whoever perceives the Arabic linguistic heritage will find its examples present in the folds of those texts. Repetition is one of the linguistic methods employed by the Arabs in their transcripts, or their sayings for several semantic goals that are delivered by the originator of the text to the recipient or listener. the meaning of repetition in the language, its derivation, and its concept in the terminology. The researcher also stated the difference between language, and repetition, confirmation, and recurrence, and mentioned its semantic importance, and its types. according to Kamal Pasha, the impact of semantic repetition in the interpretation of verses, the intended meanings of repetition added to the lexical meaning of the terminology of the Holy Qur’an, its apparent meaning, and the subconscious, in line with the textual format of the Holy Qur’an.